Catalyst as well as preparation method and application thereof
By preparing the M-N/C catalyst and the heat treatment of the silicon dioxide impurities, the problem of low performance of the existing non-valuable metal catalysts is solved, and the commercial goal of high-efficiency catalytic performance and low cost in fuel cells is achieved.
Patent Information
- Application Number
- CN202411320762.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The performance of existing non-precious metal catalysts in fuel cell testing is lower than that of Pt-based materials, making it difficult to achieve low-cost commercialization.
The M-N/C catalyst is prepared by dispersing iron source, manganese source, nitrogen-rich organic precursor and silica in a solvent, and the performance of the catalyst is improved by heat treatment and removal of silica impurities.
The catalyst prepared by this method has shown good catalytic performance in fuel cell tests, can effectively realize the three-phase boundary, reduce costs, and its performance is close to that of commercial Pt/C catalysts.
Smart Images

Figure CN119361720A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and in particular to a catalyst and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is a widely used fuel cell with good prospects. Cost is one of the key issues for the widespread application of PEMFC. In PEMFC, Pt and its alloys are generally used as the main catalyst materials. Pt is a precious metal, and the cost of material application is relatively high. In addition, the domestic Pt reserves are not high. A major development direction of existing fuel cells is to reduce the Pt load or use non-precious metal catalysts. In order to effectively solve the low-cost commercialization of fuel cells in the long term, non-precious metal catalysts must be developed.
[0003] Researchers are committed to studying non-precious metal catalysts, including non-precious metal oxides, non-precious metal nitrides and nitrogen oxides, non-precious metal carbonitrides, non-precious metal sulfides, N-doped carbon materials, and MN / C (M is Fe, Co, etc.) catalysts. The goal is to innovate the fuel cell catalyst industry and develop efficient and stable non-precious metal catalysts that can replace Pt-based catalysts. In terms of the current development of non-precious metal catalysts, Fe-N / C catalysts show relatively impressive catalytic performance and have become the most likely type of catalyst to replace Pt-based catalysts.
[0004] Although the non-platinum catalysts themselves have shown improved catalytic activity, their performance in actual fuel cell tests is still lower than that of Pt-based materials. Summary of the invention
[0005] The present application provides a catalyst and a preparation method and application thereof to improve the performance of a non-platinum catalyst in actual fuel cell testing.
[0006] In a first aspect, the present application provides a method for preparing a catalyst, the method comprising:
[0007] dispersing an iron source, a manganese source, a nitrogen-rich organic precursor and silicon dioxide in a solvent to obtain a mixed paste;
[0008] Drying the mixed paste to obtain an intermediate powder;
[0009] The intermediate powder is subjected to a first heat treatment, and then silicon dioxide in the intermediate powder after the first heat treatment is removed to obtain a crude catalyst;
[0010] The crude catalyst is subjected to a second heat treatment to obtain a catalyst.
[0011] As an optional implementation manner, the molar ratio of iron to manganese in the iron source and the manganese source is (1-2):1.
[0012] As an optional embodiment, the temperature of the second heat treatment is 1000° C. to 1100° C.; and / or
[0013] The second heat treatment time is 40 min to 50 min; and / or
[0014] The second heat treatment is performed in an atmosphere of nitrogen and / or an inert gas.
[0015] As an optional embodiment, the iron source includes iron; and / or
[0016] The manganese source comprises manganese nitrate; and / or
[0017] The nitrogen-rich organic precursor comprises at least one of nicarbazine and pipecolic acid; and / or
[0018] The surface area of the silicon dioxide is not more than 150 m 2 / g.
[0019] As an optional embodiment, the drying temperature is 80°C to 100°C; and / or
[0020] The drying time is 8 to 12 hours.
[0021] As an optional embodiment, the temperature of the first heat treatment is 900° C. to 1000° C.; and / or
[0022] The first heat treatment lasts for 80 to 100 minutes; and / or
[0023] The first heat treatment is performed in an atmosphere of nitrogen and / or an inert gas.
[0024] As an optional embodiment, the silicon dioxide in the intermediate powder is removed by immersion; and / or
[0025] The soaking liquid of the soaking comprises HF solution; and / or
[0026] The mass concentration of the HF solution is 20% to 30%; and / or
[0027] The soaking time is 20 hours to 28 hours.
[0028] In a second aspect, the present application provides a catalyst, which is prepared by the method provided in the first aspect.
[0029] In a third aspect, the present application provides a membrane electrode, wherein the membrane electrode comprises a cathode, and the cathode comprises the catalyst provided in the second aspect.
[0030] As an optional embodiment, the catalyst loading on the cathode is 2.0 mg / cm 2 ~3.0mg / cm 2 .
[0031] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0032] The method provided in the embodiment of the present application prepares the MN / C catalyst by adopting an iron source and a manganese source, and introduces Mn into the Fe-N / C catalyst. The catalyst has good catalytic performance and can realize an effective three-phase boundary when applied to the cathode catalyst layer, thereby improving the performance of the catalyst in actual fuel cell tests. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0034] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0035] Figure 1 A schematic diagram of a process for a method provided in an embodiment of the present application;
[0036] Figure 2 Polarization curve diagram of the membrane electrode formed by the catalyst provided in the examples and comparative examples of the present application. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0039] Figure 1 A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, the present application embodiment provides a method for preparing a catalyst, the method comprising:
[0040] S1. dispersing an iron source, a manganese source, a nitrogen-rich organic precursor and silicon dioxide in a solvent to obtain a mixed paste;
[0041] In some embodiments, the molar ratio of iron to manganese in the iron source and the manganese source is (1-2):1.
[0042] Doping with Mn can improve the oxygen reduction activity of Fe-doped non-Pt catalysts. The molar ratio of iron to manganese in the iron source and manganese source is controlled to be (1-2):1. If the molar ratio is too large, it will lead to fewer active sites and reduce the catalytic performance; if the molar ratio is too small, the formed catalytic layer structure will be blocked and unable to form a mass transfer channel.
[0043] Illustratively, the molar ratio of iron to manganese in the iron source and the manganese source can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, etc., and it can also be any value in the range of (1 to 2):1.
[0044] In some embodiments, the iron source comprises iron; the manganese source comprises manganese nitrate; the nitrogen-rich organic precursor comprises at least one of nicarbazine and pipecolic acid; and the surface area of the silicon dioxide is no more than 150 m 2 / g.
[0045] Specifically, in this embodiment, iron and manganese nitrates (the molar ratio of Fe to Mn can be 1:1 to 2:1), sufficient nitrogen-rich organic precursors (nicarbazine and pipecolic acid) and sufficient fumed silica (surface area ~150m 2 / g) was dispersed in water and mechanically mixed until a viscous mixed paste was obtained.
[0046] S2. The mixed paste is dried to obtain an intermediate powder;
[0047] In some embodiments, the drying temperature is 80°C to 100°C; the drying time is 8 to 12 hours. Exemplarily, the drying temperature can be 80°C, 85°C, 90°C, 95°C or 100°C, etc., and it can also be any value in the range of 80°C to 100°C. The drying time can be 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h or 12h, etc., and it can also be any value in the range of 8 to 12h.
[0048] S3. subjecting the intermediate powder to a first heat treatment, and then removing silicon dioxide from the intermediate powder after the first heat treatment to obtain a crude catalyst;
[0049] In some embodiments, the temperature of the first heat treatment is 900°C to 1000°C; the time of the first heat treatment is 80min to 100min. Exemplarily, the temperature of the first heat treatment can be 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C or 1000°C, etc., and it can also be any value in the range of 900°C to 1000°C. The time of the second heat treatment can be 80min, 82min, 84min, 86min, 88min, 90min, 92min, 94min, 96min, 98min or 100min, etc., and it can also be any value in the range of 80min to 100min.
[0050] In some embodiments, the first heat treatment is performed in an atmosphere of nitrogen and / or an inert gas atmosphere, wherein the inert gas atmosphere may be an argon atmosphere or the like.
[0051] In some embodiments, the silicon dioxide in the intermediate powder is removed by soaking. Wherein, the soaking liquid includes HF solution; further, the mass concentration of the HF solution is 20% to 30%. Exemplarily, the mass concentration of the HF solution can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%, etc., and it can also be any value within the range of 20% to 30%. The soaking time is 20h to 28h, and exemplary, the soaking time can be 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h or 28h, etc.
[0052] Specifically, in this embodiment, the dried intermediate powder is heated at 950°C in N 2 The powder was heat treated in an atmosphere for 90 minutes, and then immersed in a HF solution with a mass concentration of 25% for 24 hours to remove silicon dioxide impurities, and then washed with water until the pH was ≈ 6, thereby obtaining a crude catalyst.
[0053] S4. subjecting the crude catalyst to a second heat treatment to obtain a catalyst.
[0054] In some embodiments, the temperature of the second heat treatment is 1000° C. to 1100° C.; the time of the second heat treatment is 40 min to 50 min.
[0055] After the catalyst is heat treated at high temperature, the reaction tends to a four-electron reaction mechanism, which enhances the activity and stability of such catalysts. The temperature is controlled at 1000℃~1100℃. Too low temperature will lead to incomplete reaction, and too high temperature will lead to larger product grains and smaller specific surface area, which will affect the performance of the product.
[0056] Exemplarily, the temperature of the second heat treatment may be 1000° C., 1010° C., 1020° C., 1030° C., 1040° C., 1050° C., 1060° C., 1070° C., 1080° C., 1090° C. or 1100° C., etc., and it may also be any value in the range of 1000° C. to 1100° C. The time of the second heat treatment may be 40 min, 41 min, 42 min, 43 min, 44 min, 45 min, 46 min, 47 min, 48 min, 49 min or 50 min, etc., and it may also be any value in the range of 40 min to 50 min.
[0057] In some embodiments, the atmosphere of the second heat treatment is a nitrogen atmosphere and / or an inert gas atmosphere, wherein the inert gas atmosphere may be an argon atmosphere or the like.
[0058] Specifically, in this embodiment, the crude catalyst is heated to 1000°C to 1100°C in N 2 The catalyst Fe-Mn-N / C was obtained by heat treatment in an atmosphere for 45 minutes.
[0059] Based on a general inventive concept, an embodiment of the present application further provides a catalyst, which is prepared by the method provided above.
[0060] The catalyst is prepared based on the above method. The specific steps of the method can refer to the above embodiments. Since the catalyst adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0061] Based on a general inventive concept, an embodiment of the present application further provides a membrane electrode, wherein the membrane electrode comprises a cathode, and the cathode comprises the catalyst provided above.
[0062] In some embodiments, the membrane electrode can be prepared by transfer printing. Specifically, the anode can be prepared by using a commercial Pt / C catalyst, and the cathode can be prepared by using the catalyst provided above. The Pt loading of the anode is 0.1 mg / cm 2 , the cathode catalyst loading is 2.0~3.0mg / cm 2(That is, 2.0-3.0 mg of Fe-Mn-N / C catalyst material is used per square centimeter of active area). The transfer temperature is 130-150°C, the pressure is 1.2MPa-2.0MPa, and the pressure holding time is 120s-150s.
[0063] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0064] Example 1
[0065] A catalyst, the preparation process of which is as follows:
[0066] Iron and manganese nitrates (the molar ratio of Fe to Mn can be 1:1), sufficient nitrogen-rich organic precursors (nicarbazine and pipecolic acid) and sufficient fumed silica (surface area ~150m 2 / g) was dispersed in water and mechanically mixed until a viscous mixed paste was obtained.
[0067] The mixture was dried at 90°C for 10 h to obtain an intermediate powder.
[0068] The dried powder was then heated at 950 °C in N 2 After heat treatment in atmosphere for 90 min, the powder was then immersed in 25 wt.% HF solution for 24 h to remove silica impurities, and then washed with water until the pH was ≈ 6, thereby obtaining a crude catalyst.
[0069] Then, the crude catalyst was heated at 1000 °C in N 2 After heat treatment in atmosphere for 45 minutes, the catalyst Fe-Mn-N / C was obtained.
[0070] Example 2
[0071] A catalyst, the preparation process of which is as follows:
[0072] Iron and manganese nitrates (the molar ratio of Fe to Mn can be 2:1), sufficient nitrogen-rich organic precursors (nicarbazine and pipecolic acid) and sufficient fumed silica (surface area ~150m 2 / g) was dispersed in water and mechanically mixed until a viscous mixed paste was obtained.
[0073] The mixture was dried at 90°C for 10 h to obtain an intermediate powder.
[0074] The dried powder was then heated at 950 °C in N 2 After heat treatment in atmosphere for 90 min, the powder was then immersed in 25 wt.% HF solution for 24 h to remove silica impurities, and then washed with water until the pH was ≈ 6, thereby obtaining a crude catalyst.
[0075] Then, the crude catalyst was heated at 1000 °C in N 2 After heat treatment in atmosphere for 45 minutes, the catalyst Fe-Mn-N / C was obtained.
[0076] Example 3
[0077] A catalyst, the preparation process of which is as follows:
[0078] Iron and manganese nitrates (the molar ratio of Fe to Mn can be 2:1), sufficient nitrogen-rich organic precursors (nicarbazine and pipecolic acid) and sufficient fumed silica (surface area ~150m 2 / g) was dispersed in water and mechanically mixed until a viscous mixed paste was obtained.
[0079] The mixture was dried at 90°C for 10 h to obtain an intermediate powder.
[0080] The dried powder was then heated at 950 °C in N 2 After heat treatment in atmosphere for 90 min, the powder was then immersed in 25 wt.% HF solution for 24 h to remove silica impurities, and then washed with water until the pH was ≈ 6, thereby obtaining a crude catalyst.
[0081] Then, the crude catalyst was heated at 1050 °C in N 2 After heat treatment in atmosphere for 45 minutes, the catalyst Fe-Mn-N / C was obtained.
[0082] Example 4
[0083] A catalyst, the preparation process of which is as follows:
[0084] Iron and manganese nitrates (the molar ratio of Fe to Mn can be 0.5:1), sufficient nitrogen-rich organic precursors (nicarbazine and pipecolic acid) and sufficient fumed silica (surface area ~150m 2 / g) was dispersed in water and mechanically mixed until a viscous mixed paste was obtained.
[0085] The mixture was dried at 90°C for 10 h to obtain an intermediate powder.
[0086] The dried powder was then heated at 950 °C in N 2After heat treatment in atmosphere for 90 min, the powder was then immersed in 25 wt.% HF solution for 24 h to remove silica impurities, and then washed with water until the pH was ≈ 6, thereby obtaining a crude catalyst.
[0087] Then, the crude catalyst was heated at 1000 °C in N 2 After heat treatment in atmosphere for 45 minutes, the catalyst Fe-Mn-N / C was obtained.
[0088] Example 5
[0089] A catalyst, the preparation process of which is as follows:
[0090] Iron and manganese nitrates (the molar ratio of Fe to Mn can be 3:1), sufficient nitrogen-rich organic precursors (nicarbazine and pipecolic acid) and sufficient fumed silica (surface area ∼150 m 2 / g) was dispersed in water and mechanically mixed until a viscous mixed paste was obtained.
[0091] The mixture was dried at 90°C for 10 h to obtain an intermediate powder.
[0092] The dried powder was then heated at 950 °C in N 2 After heat treatment in atmosphere for 90 min, the powder was then immersed in 25 wt.% HF solution for 24 h to remove silica impurities, and then washed with water until the pH was ≈ 6, thereby obtaining a crude catalyst.
[0093] Then, the crude catalyst was heated at 1000 °C in N 2 After heat treatment in atmosphere for 45 minutes, the catalyst Fe-Mn-N / C was obtained.
[0094] Example 6
[0095] A catalyst, the preparation process of which is as follows:
[0096] Iron and manganese nitrates (the molar ratio of Fe to Mn can be 2:1), sufficient nitrogen-rich organic precursors (nicarbazine and pipecolic acid) and sufficient fumed silica (surface area ~150m 2 / g) was dispersed in water and mechanically mixed until a viscous mixed paste was obtained.
[0097] The mixture was dried at 90°C for 10 h to obtain an intermediate powder.
[0098] The dried powder was then heated at 950 °C in N 2After heat treatment in atmosphere for 90 min, the powder was then immersed in 25 wt.% HF solution for 24 h to remove silica impurities, and then washed with water until the pH was ≈ 6, thereby obtaining a crude catalyst.
[0099] The crude catalyst was then heated at 950 °C in N 2 After heat treatment in atmosphere for 45 minutes, the catalyst Fe-Mn-N / C was obtained.
[0100] Example 7
[0101] A catalyst, the preparation process of which is as follows:
[0102] Iron and manganese nitrates (the molar ratio of Fe to Mn can be 2:1), sufficient nitrogen-rich organic precursors (nicarbazine and pipecolic acid) and sufficient fumed silica (surface area ~150m 2 / g) was dispersed in water and mechanically mixed until a viscous mixed paste was obtained.
[0103] The mixture was dried at 90°C for 10 h to obtain an intermediate powder.
[0104] The dried powder was then heated at 950 °C in N 2 After heat treatment in atmosphere for 90 min, the powder was then immersed in 25 wt.% HF solution for 24 h to remove silica impurities, and then washed with water until the pH was ≈ 6, thereby obtaining a crude catalyst.
[0105] Then, the crude catalyst was heated at 1100 °C in N 2 After heat treatment in atmosphere for 45 minutes, the catalyst Fe-Mn-N / C was obtained.
[0106] Example 8
[0107] A catalyst, the preparation process of which is as follows:
[0108] Iron and manganese nitrates (the molar ratio of Fe to Mn can be 2:1), sufficient nitrogen-rich organic precursors (nicarbazine and pipecolic acid) and sufficient fumed silica (surface area ~150m 2 / g) was dispersed in water and mechanically mixed until a viscous mixed paste was obtained.
[0109] The mixture was dried at 90°C for 10 h to obtain an intermediate powder.
[0110] The dried powder was then heated at 950 °C in N 2After heat treatment in atmosphere for 90 min, the powder was then immersed in 25 wt.% HF solution for 24 h to remove silica impurities, and then washed with water until the pH was ≈ 6, thereby obtaining a crude catalyst.
[0111] Then, the crude catalyst was heated at 1200 °C in N 2 After heat treatment in atmosphere for 45 minutes, the catalyst Fe-Mn-N / C was obtained.
[0112] Comparative Example 1
[0113] A certain brand of Pt / C catalyst particles sold on the market was tested.
[0114] The physical property parameters of the catalysts provided in each embodiment and comparative example were tested, and the results are shown in the following table:
[0115]
[0116]
[0117] As can be seen from the above table, compared with the best performance and most widely used Pt / C catalyst in fuel cell membrane electrode, the non-Pt catalyst prepared in this application shows better performance than the commonly used Pt / C catalyst in the market in some aspects, such as surface area, pore size, etc. In addition, since no precious metals are used, the cost is significantly superior to Pt / C.
[0118] The catalysts provided in each embodiment and comparative example were prepared into a cathode catalyst layer and a membrane electrode. The specific preparation process was as follows: a commercial Pt / C catalyst was used to prepare an anode, and the anode Pt loading was 0.1 mg / cm 2 , the cathode catalyst loading is 2.0~3.0mg / cm 2 ; The transfer temperature is 140°C, the pressure is 1.6MPa, and the holding time is 135s. The physical properties of each membrane electrode are tested, and the results are shown in the following table.
[0119]
[0120] It can be seen from the above table that compared with the Pt / C catalyst, which has the best performance and is the most widely used in fuel cell membrane electrode, the non-Pt catalyst prepared in this application has reached the level of Pt / C catalyst in terms of pore structure proportion and size.
[0121] The electrical performance of the membrane electrode made of the catalyst provided in each embodiment and comparative example was tested. The results are as follows: Figure 2As shown in the figure, it can be seen that the power generation performance of the non-Pt catalyst (sample 1 to sample 8) has an obvious corresponding relationship with the physical and chemical properties of the catalyst. In addition, the performance of the non-Pt catalyst of this patent is close to that of the existing commercial Pt / C catalyst. In addition, since the Pt catalyst prepared in this patent does not use precious metal materials, it has certain cost advantages.
[0122] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0123] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b and c can be single or multiple.
[0124] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a catalyst, characterized in that: The method comprises: dispersing an iron source, a manganese source, a nitrogen-rich organic precursor and silicon dioxide in a solvent to obtain a mixed paste; Drying the mixed paste to obtain an intermediate powder; The intermediate powder is subjected to a first heat treatment, and then silicon dioxide in the intermediate powder after the first heat treatment is removed to obtain a crude catalyst; The crude catalyst is subjected to a second heat treatment to obtain a catalyst.
2. The method for preparing a catalyst according to claim 1, characterized in that: The molar ratio of iron to manganese in the iron source and the manganese source is (1-2):
1.
3. The method for preparing the catalyst according to claim 1, characterized in that: The temperature of the second heat treatment is 1000°C to 1100°C; and / or The second heat treatment time is 40 min to 50 min; and / or The second heat treatment is performed in an atmosphere of nitrogen and / or an inert gas.
4. The method for preparing the catalyst according to claim 1, characterized in that: The iron source comprises iron; and / or The manganese source comprises manganese nitrate; and / or The nitrogen-rich organic precursor comprises at least one of nicarbazine and pipecolic acid; and / or The surface area of the silicon dioxide is not more than 150 m 2 / g.
5. The method for preparing the catalyst according to claim 1, characterized in that: The drying temperature is 80°C to 100°C; and / or The drying time is 8 to 12 hours.
6. The method for preparing a catalyst according to claim 1, characterized in that: The temperature of the first heat treatment is 900°C to 1000°C; and / or The first heat treatment lasts for 80 to 100 minutes; and / or The first heat treatment is performed in an atmosphere of nitrogen and / or an inert gas.
7. The method for preparing a catalyst according to claim 1, characterized in that: The silicon dioxide in the intermediate powder is removed by immersion; and / or The soaking liquid of the soaking comprises HF solution; and / or The mass concentration of the HF solution is 20% to 30%; and / or The soaking time is 20 hours to 28 hours.
8. A catalyst, characterized in that The catalyst is prepared by the method according to any one of claims 1 to 7.
9. A membrane electrode, characterized in that: The membrane electrode comprises a cathode, and the cathode comprises the catalyst according to claim 8.
10. The membrane electrode according to claim 9, characterized in that: The catalyst loading on the cathode is 2.0 mg / cm 2 ~3.0mg / cm 2 .
Citation Information
Patent Citations
Metal-free nitrogen-doped functionalized mesoporous carbon catalyst and preparation method and applications thereof
CN103566961A
Preparation method of carbon based catalyst with high graphitization degree and used for fuel cell cathode
CN104289242A
Production method of atomically-dispersed metal and nitrogen co-doped carbon-based oxygen reduction reaction catalyst
CN110013881A
Direct grown carbon nanotube-based non-noble metal fuel cell catalyst and preparation method thereof
CN113054209A
Nitrogen-doped porous carbon-loaded monatomic catalyst as well as preparation method and application thereof
CN116885215A